Whole-body Electromyostimulation plus Caloric Restriction in Metabolic Syndrome - Bellia, Alfonso; Ruscello, Bruno; Bolognino, Rolando; Briotti, Gianluca; Gabrielli, Paolo Roberto; Silvestri, Adriano; Rosazza, Cristina; Ambruoso, Francesca; Lombardo, Mauro; Bernardini, Andrea; Calabrese, Cosimo; Lauro, Davide; D’Ottavio, Stefano (International Journal of Sports Medicine, 2020)
We investigated early effects of Whole-Body Electromyostimulation added to hypocaloric diet on metabolic syndrome features in sedentary middle-aged individuals. We randomly assigned 25 patients to Whole-Body Electromyostimulation plus caloric restriction or caloric restriction alone for 26 weeks. Anthropometrics, blood pressure, fasting glucose and insulin, HOMA-IR, glycated hemoglobin, lipids, uric acid, creatinphosphokynase, C-reactive protein were assessed. Body composition was evaluated with direct-segmental, multi-frequency Bioelectrical Impedance Analysis. Both groups lost approximately 10% of weight, with similar effects on waist circumference and fat mass. Change in free-fat mass was significantly different between groups (caloric restriction −1.5±0.2 vs. Whole-Body Electromyostimulation plus caloric restriction +1.1±0.4 kg, p=0.03). Whole-Body Electromyostimulation plus caloric restriction group experienced greater percent reductions in insulin (−45.5±4.4 vs. −28.2±3.6%, p=0.002), HOMA-IR (–51.3±3.2 vs. –25.1±1.8%, p=0.001), triglycerides (−22.5±2.9 vs. −4.1±1.6%, p=0.004) and triglycerides/HDL (p=0.028). Subjects trained with Whole-Body Electromyostimulation had also significant improvement in systolic pressure (138±4 vs. 126±7 mmHg, p=0.038). No discontinuations for adverse events occurred. In middle-aged sedentary subjects with the metabolic syndrome, Whole-Body Electromyostimulation with caloric restriction for 26 weeks can improve insulin-resistance and lipid profile compared to diet alone. Further studies are needed to ascertain long-term efficacy and feasibility of this approach in individuals with the metabolic syndrome.
Keywords: whole-body electromyostimulation; resistance training; metabolic syndrome; cardiovascular risk; insulin-resistance; overweight